2000
DOI: 10.1111/j.1748-5827.2000.tb03204.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gestational age in medium and small size bitches using ultrasonographic fetal measurements

Abstract: A study was undertaken to estimate gestational age, in terms of days from parturition, in medium and small size dogs by ultrasonographic examination. Serial ultrasonographic examinations were performed in four medium size pregnant bitches throughout two consecutive pregnancies and three small size pregnant bitches throughout one pregnancy, in order to determine the range of variation in the size of selected fetal structures throughout gestation. Formulae were derived to estimate the expected delivery date for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
120
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(136 citation statements)
references
References 8 publications
4
120
0
9
Order By: Relevance
“…1990; Yeager et al. 1992; Luvoni and Grioni 2000). Determination of ICC allowed accurate prediction of parturition date within ±2 days in 80% of the bitches examined (Son et al.…”
Section: Current Options For Prediction Of Parturition Datementioning
confidence: 99%
See 1 more Smart Citation
“…1990; Yeager et al. 1992; Luvoni and Grioni 2000). Determination of ICC allowed accurate prediction of parturition date within ±2 days in 80% of the bitches examined (Son et al.…”
Section: Current Options For Prediction Of Parturition Datementioning
confidence: 99%
“…BPD is the most accurate parameter during late pregnancy (<25 days before parturition) and allows prediction of parturition date within ±2 days in 81–88% of bitches (England et al. 1990; Luvoni and Grioni 2000; Luvoni and Beccaglia 2006).…”
Section: Current Options For Prediction Of Parturition Datementioning
confidence: 99%
“…Ultrasonography is a useful imaging modality for determining pregnancy [4,7,13], estimating the litter size [5,13], fetal development [14, 18], uterine examination after parturition [16], a reproductive examination and the direct detection of ovulation [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Sabbagha et al [18] reported the change of the biparietal diameter during pregnancy in the rhesus monkey. Luvoni et al [14] evaluated biparietal diameter, gestational sac and placental thickness for estimation of gestational age in the bitch. White et al [22] reported the relation of biparietal diameter, trunk diameter, crown-rump length and uterine diameter with gestational age in the cattle.…”
mentioning
confidence: 99%